Total Quality Management at Private Boarding High School in Yogyakarta - Saadah, Ummu; Wijayanti, Wiwik (Lectura : Jurnal Pendidikan, 2025)
Sekolah Menengah Atas (SMA) Muhammadiyah Boarding School (MBS) Sleman is one of the 9 educational institutions that receive diploma equivalence (Muadalah) from Al-Azhar University Cairo. That case made SMA MBS Sleman have unique characteristics and distinct advantages over other boarding-based schools in the Yogyakarta. This study aimed to investigate in depth the characteristics of a total quality management at SMA MBS Sleman. This research employed a qualitative approach, utilizing a case study type. The data collection technique used interviews, observations, and documentation. Data analysis used the interactive model by Miles, Huberman, and Saldana. The results of this study indicated that the characteristics of total quality management at SMA MBS were demonstrated by (1) customer focus: excellent relationships with customers, customer needs surveys, the implementation of an integrated curriculum, and adequate facilities and infrastructure; (2) total involvement: the formation of small teams in program implementation and the involvement of stakeholders in policy formulation; (3) measurement: the presence of a quality assurance team at the pesantren level, reporting by teachers and educational staff regarding their respective duties and responsibilities, and regular leadership meetings; (4) commitment: the commitment to quality has been established since the beginning of its establishment, training programs for teachers and staff, the school consistently strived to provide quality facilities and services for the school community; and (5) continuous improvement: improvements in the planning, and improvements in implementation. The above-stated result suggests that SMA MBS Sleman possesses all the characteristics of total quality management.